Standardization of Processing Techniques for Karonda (Carissa carandas) Products for Commercial Utilization (Indian Journal of Arid Horticulture, 2025)
Karonda (Carissa carandas L.) is an underutilized indigenous fruit crop of India, well adapted to arid and semi-arid regions. Due to its astringent taste, it is not widely consumed as a dessert fruit, yet it is a rich source of essential vitamins and minerals. The ripe fruit possesses antioxidant properties and has been reported to be beneficial in treating diseases such as bilious disorders (Watt, 1972) and intestinal ailments (Vasni, 1986).Karonda has immense potential for processing into value-added products such as preserves, jam, candy, juices, and pickles (Chandra & Jindal, 2001). However, a significant portion of the harvest is lost due to seasonal glut, leading to reduced market prices and wastage, with post-harvest losses ranging from 30-40%. The fruit’s high acidity makes it less popular for direct consumption, emphasizing the need for value addition to enhance its commercial utilization (Parvathi & Anby, 1997).Given the perishable nature of karonda, its preservation and conversion into processed products with extended shelf life is crucial. Despit its economic potential, limited research has been conducted on the standardization of processing techniques for karonda-based products. This study aims to develop and standardize techniques for producing candy, squash, jelly, and jam with improved storage stability and consumer acceptability.
Keywords: methodology; Karonda